2017
DOI: 10.3233/cbm-170017
|View full text |Cite
|
Sign up to set email alerts
|

Nephroblastoma overexpressed gene expression and its prognostic implications of clinical outcomes in renal cell carcinoma patients

Abstract: Our data suggested that NOV down-regulation might be a biomarker for RCC but its positivity might be an indicator of poor prognosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…By applying a series of bioinformatics methods to explore gene expression, we identified 351 genes involved in renal insufficiency in geriatric multimorbidity patients. Among these genes enriched go biological process terms, which have so far been shown to be primarily associated with renal insufficiency iucluding cytokine-mediated signaling pathway [ 30 ], signal transduction [ 31 ], negative regulation of apoptotic process [ 32 ], positive regulation of gene expression [ 33 ], response to drugs [ 34 ], positive regulation Of transcription by RNA polymerase II [ 35 ], inflammatory response [ 36 ], response to lipopolysaccharide [ 37 ], cellular protein metabolic process [ 38 ] and response to hypoxia [ 39 ]. In addition, the results of KEGG pathway analysis corresponding to 351 genes related to renal insufficiency including cytokine-cytokine receptor interaction [ 40 ], AGE-RAGE signaling pathways in diabetic complications [ 41 ], PI3K-Akt signaling pathway [ 42 ], HIF-1 signaling pathway [ 42 ], metabolic pathways [ 43 ], proteoglycans in cancer [ 44 ], transcriptional misregulation in cancer [ 45 ], fluid shear stress and atherosclerosis [ 46 ] and Human cytomegalovirus infection [ 47 ].…”
Section: Discussionmentioning
confidence: 99%
“…By applying a series of bioinformatics methods to explore gene expression, we identified 351 genes involved in renal insufficiency in geriatric multimorbidity patients. Among these genes enriched go biological process terms, which have so far been shown to be primarily associated with renal insufficiency iucluding cytokine-mediated signaling pathway [ 30 ], signal transduction [ 31 ], negative regulation of apoptotic process [ 32 ], positive regulation of gene expression [ 33 ], response to drugs [ 34 ], positive regulation Of transcription by RNA polymerase II [ 35 ], inflammatory response [ 36 ], response to lipopolysaccharide [ 37 ], cellular protein metabolic process [ 38 ] and response to hypoxia [ 39 ]. In addition, the results of KEGG pathway analysis corresponding to 351 genes related to renal insufficiency including cytokine-cytokine receptor interaction [ 40 ], AGE-RAGE signaling pathways in diabetic complications [ 41 ], PI3K-Akt signaling pathway [ 42 ], HIF-1 signaling pathway [ 42 ], metabolic pathways [ 43 ], proteoglycans in cancer [ 44 ], transcriptional misregulation in cancer [ 45 ], fluid shear stress and atherosclerosis [ 46 ] and Human cytomegalovirus infection [ 47 ].…”
Section: Discussionmentioning
confidence: 99%
“…NOV plays important biological functions in regulating cell apoptosis, tumor invasion, and tumor metastasis, etc. [11]. Some studies have shown that NOV exerts an inhibitory function in some malignant solid tumors [13][14][15][16].…”
Section: Introductionmentioning
confidence: 99%